The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/srin.201600028
|View full text |Cite
|
Sign up to set email alerts
|

Tensile Behavior of Cast and Electron Beam Welded Interstitially Strengthened High-Alloy TRIP Steel

Abstract: Due to their enormous potential for energy absorption, high-alloy TRIP/TWIP steels are designed to fulfill contrary requirements of crash-relevant structures such as strength, toughness, and ductility and even excellent weldability. To further optimize these mechanical properties and reduce the production costs at the same time, high-alloy TRIP/TWIP steels with an increased content of carbon and nitrogen and decreased amount of nickel are produced. The mechanical properties of the base materials and the capabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
2

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
(44 reference statements)
0
1
2
Order By: Relevance
“…Thus, it can be said that soften zones affected the tensile strength of the joinings. observed no significant influence on the mechanical properties (tensile strength and elongation) of electron beam welded metal compared to the base metal [19]. On the contrary, in this present study, it was seen that the highest tensile strength (averagely 840 MPa) and elongation (averagely 23%) values were observed at the TRIP 800-TRIP 800 welded joint.…”
Section: Tensile Strength Testcontrasting
confidence: 84%
See 2 more Smart Citations
“…Thus, it can be said that soften zones affected the tensile strength of the joinings. observed no significant influence on the mechanical properties (tensile strength and elongation) of electron beam welded metal compared to the base metal [19]. On the contrary, in this present study, it was seen that the highest tensile strength (averagely 840 MPa) and elongation (averagely 23%) values were observed at the TRIP 800-TRIP 800 welded joint.…”
Section: Tensile Strength Testcontrasting
confidence: 84%
“…High Ni rate decreased both FZ and HAZ [28]. Various researchers reported that slower welding speeds caused homogeneous hardness profile between FZ and base metal at TRIP steel welded by using EBW [19]. However, in the present study, the welding speed was slower than the study mentioned above (the speed in the present study is approximately 3 mm/s slower than theirs) and heterogeneous hardness patterns were observed at the base metal and FZ.…”
Section: Microhardness Testcontrasting
confidence: 74%
See 1 more Smart Citation